2012
DOI: 10.1111/j.1365-2494.2012.00884.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of functional groups and species richness on biomass constituents relevant for combustion: results from a grassland diversity experiment

Abstract: Grassland biomass has been identified as a potential energy source. The combustion of mature and fibrous biomass, as occurs in extensive grasslands managed with low cutting frequencies, is one possible conversion technique. This study tested the relationship between plant diversity and biomass constituents relevant for combustion, as they determine energy content, energy yield and emission and corrosion risks. The biomass from a biodiversity experiment, with a species richness (SR) gradient of 1–60 species fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 60 publications
4
19
0
Order By: Relevance
“…If this were true, it would be reflected, among other factors, in the dominance structure of the plots; however, Khalsa et al . () showed no notable change in dominance structure with increasing SR. Furthermore, the independence of SR from functional‐group presence/absence could be proven by fitting each functional‐group term individually before SR in the hierarchy of the statistical model.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…If this were true, it would be reflected, among other factors, in the dominance structure of the plots; however, Khalsa et al . () showed no notable change in dominance structure with increasing SR. Furthermore, the independence of SR from functional‐group presence/absence could be proven by fitting each functional‐group term individually before SR in the hierarchy of the statistical model.…”
Section: Discussionmentioning
confidence: 84%
“…Calculated from the data presented in Khalsa et al . (), the C/N ratio of the all functional‐group mixtures (first cut: 27·6; second cut: 24·5) was near the optimum.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Khalsa et al [32] found grass from extensive management to have an ash content ranging between 5.3% and 22% DM, depending on plant species composition and harvest date, with an average of 9.4% DM. Piepenschneider et al [6] observed the mean ash content in untreated urban leaf litter to be at 13.8% DM, while the range was between 6.7% and 19.4% DM, depending on tree species and soil contamination.…”
Section: Fuel Characteristicsmentioning
confidence: 99%